ROOTING OF STEM CUTTINGS OF KUDZU - BORTOLINI, Michele Fernanda; DOBIGNIES, Alain; ZUFELLATO-RIBAS, Kátia Christina; CARPANEZZI, Antonio Aparecido; TAVARES, Fernando Rodrigues (Scientia Agraria, 2007)
Kudzu (Pueraraia lobata (Willd) Ohwi) is a semihardwood legume of low habitat, from east and southeast of the Asian, used for animal feeding as green fertilizer, for medicinal and culinary ends, to paper and woven manufacturing and it can be destined to the recovery of degraded areas. For pioneering to be considered, with efficiency in the soils covering, As your the sexual propagation of the species is made unfeasible by the scarce flowering and for the low seeds production, the vegetative propagation be can alternative for the production of your seedlings. During 2003 works were accomplished in Embrapa Florestas, in Colombo – PR, seeking the kudzu vegetative propagation, with cuttings made 12 cm of length, diameter 0,7 cm, without leaves and a yolk in the upper, colleted in the four seasons. As previous sanitary treated the cuttings were immersed in solution of sodium hipiclorite (0,5%) for 5 minutes, and in benomyl (0,5 g L–1) for 15 minutes. The basis of cuttings were treated with 0, 500, 1000 and 1500 mg L–1 of indolebutyric acid (IBA), planted in polypropylene boxes with vermiculite and remaining in a greenhouse under intermittent mist during for 30 days. Data were analyzed using a completely randomized design with 4 treatments, 4 replications of 24 cuttings each, totaling 384 cuttings for season. The best rooting percentages were detected with 1000 mg L–1 (61,46 %) and 1500 mg L–1 IBA (73,96 %), in summer, and 1500 mg L–1 IBA (62,06%) in spring. The use of the IBA it was shown efficient in the rooting of cuttings of Kudzu, any seasons, except in winter.